The Impact of Corporate Governance on the Cost of Equity in Nepalese Commercial Banks - Pandey, Bivek; Bhattarai, Anish; Pradhan, Sumit (Nepalese Journal of Finance, 2024)
The study examines the impact of corporate governance on the cost of equity in Nepalese commercial banks. Stock dividend and cash dividend are selected as the dependent variables. The selected independent variables are board independence, institutional ownership, female director, audit committee size, board size, government ownership, and number of meeting. The study is based on secondary data of 15 commercial banks with 105 observations for the period from 2015/16 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance on the cost of equity in Nepalese commercial banks.The study showed that board independence has a negative impact on stock dividend and cash dividend. It indicates that increase in number of independent directors on the board leads to decrease in stock dividend and cash dividend. Similarly, institutional ownership has a positive impact on stock dividend and cash dividend. It indicates that higher the number of shares held by the entities, higher would be the stock dividend and cash dividend. Likewise, female board of director has a positive impact on stock dividend and cash dividend. It indicates that presence of female director in the board leads to increase in stock dividend and cash dividend. Further, audit committee size has a positive impact on stock dividend and cash dividend. It indicates that increase in audit committee members leads to increase in stock dividend and cash dividend. In addition, board size has a negative impact on stock dividend and cash dividend. It indicates that higher the board size, lower would be the stock dividend and cash dividend. Likewise, government ownership has a negative impact on stock dividend and cash dividend. It indicates that higher the government ownership, lower would be the stock dividend and cash dividend. Moreover, number of meeting has a positive impact on stock dividend and cash dividend. It indicates that increase in the number of board meetings leads to increase in stock dividend and cash dividend.